PENGARUH PERENDAMAN DAN DERAJAT DERAJAT KEASAMAN SALIVA TERHADAP PERUBAHAN WARNA PADA BASIS GIGI TIRUAN LEPASAN THERMOPLASTIC NYLON - , PAUL SUGIYO, Prof. Dr. Haryo Mustiko Dipoyono, drg., M.S., Sp.Pros(K) ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Thermoplastic nylon which is used as a removable denture base material will show unexpected discoloration after a few months. This discoloration somehow will affect the satisfaction and performance of prosthesis. The purpose of this study is to determine the effect of immersion and acidity saliva on color changes the removable dentures base of thermoplastic nylon. This study used 24 thermoplastic nylon square plates which had a size of 10x10x1 mm. The samples were divided into three groups, each group consist of 8 plates thermoplastic nylon. Then the color was measured with UV-Vis spectrophotometer pharmaspec, Shimadzu, Kyoto, Japan. Each group sample was immersed in artificial saliva fluids, group I in the saliva pH4, group II in the saliva pH6, and group III in the saliva pH8, in 48 hours. After soaking in all of the sample groups, and then the color were measured. Data were analyzed using two-way ANOVA and followed Least Square Difference (LSD) test. The result showed that : 1) there was a significant difference in color changes of thermoplastic nylon before and after immersion in the saliva pH4 and pH8 while 48 hours (p<0.05), 2) there was a significant difference in color changes of thermoplastic nylon after immersion in the saliva pH4 and pH8 (p<0.05).The conclusions of this study were: 1 immersion in the saliva pH4 and pH8 during 48 hours effected to color changes of thermoplastic nylon, 2) the acidity of saliva pH4 most effected to color changes of thermoplastic nylon.